ADR visualization: A generalized framework for ranking large-scale scientific data using Analysis-Driven Refinement - Nouanesengsy, Boonthanome; Woodring, Jonathan; Patchett, John; Myers, Kary; Ahrens, James (2014 IEEE 4th Symposium on Large Data Analysis and Visualization (LDAV), 2014)
Prioritization of data is necessary for managing large-scale scientific data, as the scale of the data implies that there are only enough resources available to process a limited subset of the data. For example, data prioritization is used during in situ triage to scale with bandwidth bottlenecks, and used during focus+context visualization to save time during analysis by guiding the user to important information. In this paper, we present ADR visualization, a generalized analysis framework for ranking large-scale data using Analysis-Driven Refinement (ADR), which is inspired by Adaptive Mesh Refinement (AMR). A large-scale data set is partitioned in space, time, and variable, using user-defined importance measurements for prioritization. This process creates a prioritization tree over the data set. Using this tree, selection methods can generate sparse data products for analysis, such as focus+context visualizations or sparse data sets.